Cryptocurrency assets as a physical collateral in Indonesia - Wardoyo, Yohana Puspitasari; Hapsari, Dwi Ratna Indri (Faculty of Law, University of Muhammadiyah Malang, 2023)
Cryptocurrency investment is currently expanding quickly on a global scale as well as in Indonesia. On the one hand, cryptocurrency can be used as a medium of exchange or a form of money, which represents the original purpose of cryptocurrency. On the other hand, it can also be used as a commodity or as digital assets, also known as crypto assets. Cryptocurrency is illegal to use as money in Indonesia, but it is legal to exchange it as an asset. This study explores the legal protections for holders of collateral against the loss of crypto assets as well as how crypto assets are governed by material guarantees in Indonesia. A conceptual and statutory approach, technical analysis, and a normative legal research methodology were applied in the study. The legal material was analyzed by using the content analysis approach, which involved examining the content and legality of the material gleaned from various laws and regulations by looking at the relevant legal precedents. The discussion results discover that crypto assets fall under the definition of